Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Nasabah di Kantor Pusat PT. BPR SERANG - Anistya Vinta Desi; Mas Findi Mulya Saputra; Mulyanah Mulyanah (Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to analyze the effect of service quality and product quality on operational customer satisfaction at PT BPR Serang. The research object consisted of 100 PT BPR Serang customers who applied for credit facilities. This study employed a quantitative approach using a survey method. Data were collected through questionnaires using a five-point Likert scale and analyzed using SPSS version 26, including validity tests, reliability tests, classical assumption tests, and hypothesis testing. Supporting data were obtained through interviews with the Credit Leader and customers involved in credit agreements. The results indicate that service quality has a positive effect on customer satisfaction, reflected in the company’s ability to fulfill customer needs and expectations during the credit application process. Product quality also has a positive influence on customer satisfaction, as the credit products offered provide advantages that meet customers’ financing needs. The findings suggest that improvements in service quality and product quality simultaneously contribute to increasing customer satisfaction at PT BPR Serang.